2012 Annual Report Conference on Electrical Insulation and Dielectric Phenomena 2012
DOI: 10.1109/ceidp.2012.6378792
|View full text |Cite
|
Sign up to set email alerts
|

Determination of waiting times between successive breakdown experiments

Abstract: A common duty in high voltage engineering is the experimental determination of the breakdown voltage probability distribution of gaseous insulated electrode configurations. Due to electron detachment from negative ions in the case of electron attaching gases, the breakdown probability does not only depend on the gas and its density, but also on the ion density in the gas. If a disruptive discharge occurs in a gas gap, the number of ions in the gap is significantly increased compared to the equilibrium state at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…But, to the authors' knowledge, for C 3 F 8 only autodetachment from metastable parent anions is reported [18,19] with lifetimes in the range of 10 −11 s to 10 −8 s [20], but no detachment rates are available. The calculation of the theoretical lower limit of the statistical time lag by the volume V crit exceeding the critical field strength at the given applied voltage and the ion production rateṅ 1 (measured for SF 6 at our laboratory [49])…”
Section: Time Lagsmentioning
confidence: 99%
“…But, to the authors' knowledge, for C 3 F 8 only autodetachment from metastable parent anions is reported [18,19] with lifetimes in the range of 10 −11 s to 10 −8 s [20], but no detachment rates are available. The calculation of the theoretical lower limit of the statistical time lag by the volume V crit exceeding the critical field strength at the given applied voltage and the ion production rateṅ 1 (measured for SF 6 at our laboratory [49])…”
Section: Time Lagsmentioning
confidence: 99%
“…Various studies have been made over the time concerning the time gap between two consecutive breakdowns [14,15]. For the scope of the present work this time gap has been set to at least one minute.…”
Section: Test Conditionsmentioning
confidence: 99%
“…A certain electrode arrangement, typically needle-plane, coaxial or parallel planes, is chosen, and the breakdown voltage level is measured for a particular wave shape. A large number of breakdown experiments has to be carried out to properly account for the statistical nature of the breakdown process and it has to be ensured that each measurement is independent of the previous ones [12,13,14]. The resulting information is only valid for this configuration and wave shape and cannot be generalized or otherwise transferred.…”
Section: Introductionmentioning
confidence: 99%